Implementation of Developmental Assessment as the Basis for Individualized learning for Students with Special Needs - Muh Rijal; Hilma Rahmatillah (CV. ITTC INDONESIA, 2026)
Development assessment is a fundamental component in the education of students with special needs because it forms the basis for understanding the developmental profile, learning needs, and individual potential of students. Individualized learning or Individualized Education Program (IEP) are highly dependent on the quality of development assessments conducted by teachers. Therefore, this study aims to examine the implementation of developmental assessments for students with special needs and analyze how teachers utilize the results of these assessments in designing and adjusting individual learning. This study used a qualitative approach with a field study design. The research subjects consisted of three special education teachers representing students with autism, hearing impairments, and intellectual disabilities. Data were collected through in-depth interviews and direct observation, then analyzed inductively through data reduction, coding, and conclusion drawing to identify the main themes that emerged. The results of the study show that teachers understand developmental assessments as the main foundation of individualized learning and implement them continuously through weekly and semester assessments. Teachers use a variety of assessment media and instruments that are tailored to the sensory characteristics and developmental stages of students. Assessment results are used directly in determining learning objectives, instructional strategies, material difficulty levels, intensity of assistance, and duration of IEP. This study concludes that developmental assessment plays a strategic role as the basis for individual learning decision-making. These findings emphasize the importance of strengthening continuous, adaptive, and integrated developmental assessment practices to support responsive and equitable special education services.